Outcome of Hindfoot Nail in Old Distal Tibia and Plafond Fractures of Adult Patients in a Tertiary Care Center - Sudipta Samanta; Soumyadeep D Roy (Journal of Orthopedics and Joint Surgery)
Background: Plafond fractures and distal tibia fractures, especially those resulting from high-energy injury, are often complicated by soft tissue injury and open injuries. They are usually managed in a staged fashion with primary external fixation followed by internal fixation. From prolonged external fixation in anticipation of soft tissue healing, the patients end up with a near-stiff ankle joint and multiple failed attempts at union. Hindfoot nail (HFN) attempts to allow early mobilization of these patients by sound arthrodesis of the near-stiff ankle joint, and the study aims to evaluate the patients in terms of outcome. Materials and methods: This is a prospective study conducted on 30 subjects with old distal tibia and/or plafond fractures over a period of 2 years, and the study subjects were compared in terms of preoperative and postoperative functional, clinical, and radiological parameters. Results: The mean age of our study population was 70 years, with equal male and female distribution (1:1). The mean duration from index injury to HFN was 8.7 months. Statistically significant improvement in the modified Olerud-Molander Ankle Score (mOMAS) was observed when compared preoperatively to 1-month and 6-month follow-up (10.33 ± 7.65 vs 56.5 ± 9.84 vs 73.46 ± 5.43, respectively). The mean limb length discrepancy was 2.71 ± 1.34 cm. A total of 80% of subjects achieved sound arthrodesis of the ankle at the 6th postoperative month. Conclusion: HFN is an effective treatment option.